Equivalence of Carter diagrams - Stekolshchik, R. (Algebra and Discrete Mathematics, 2017)
We introduce the equivalence relation ρ on the set of Carter diagrams and construct an explicit transformation of any Carter diagram containing l-cycles with l>4 to an equivalent Carter diagram containing only 4-cycles. Transforming one Carter diagram Γ₁ to another Carter diagram Γ₂ we can get a certain intermediate diagram Γ′ which is not necessarily a Carter diagram. Such an intermediate diagram is called a connection diagram. The relation ρ is the equivalence relation on the set of Carter diagrams and connection diagrams. The properties of connection and Carter diagrams are studied in this paper. The paper contains an alternative proof of Carter's classification of admissible diagrams.